Model based sensitivity analysis in the determination of viscoelastic material properties using transmission measurements through circular waveguides - Bause, Fabian; Gravenkamp, Hauke; Rautenberg, Jens; Henning, Bernd
Several ultrasonic approaches for material determination are formulated in terms of an (nonlinear) inverse problem, e.g. immersion technique (Castaings et al. (2000)) or plate-waveguide techniques (Marzani et al. (2012)). In this contribution we focus on cylindrical waveguides for ultrasonic material determination and especially on the sensitivity of recorded transmission signals to the material properties. We utilize composite scaled sensitivities to determine the information content that can be achieved by the setup to certain parameters and discuss the limitations of the approach.
Keywords: Sensitivity inverse problem ultrasonic material determination

Transient modeling of ultrasonic guided waves in circular viscoelastic waveguides for inverse material characterization - Bause, Fabian; Gravenkamp, Hauke; Rautenberg, Jens; Henning, Bernd (Measurement Science and Technology)
In this contribution, we present an efficient approach for the transient and time-causal modeling of guided waves in viscoelastic cylindrical waveguides in the context of ultrasonic material characterization. We use the scaled boundary finite element method (SBFEM) for efficient computation of the phase velocity dispersion. Regarding the viscoelastic behavior of the materials under consideration, we propose a decomposition approach that considers the real-valued frequency dependence of the (visco-)elastic moduli and, separately, of their attenuation. The modal expansion approach is utilized to take the transmitting and receiving transducers into account and to propagate the excited waveguide modes through a waveguide of finite length. The effectiveness of the proposed simulation model is shown by comparison with a standard transient FEM simulation as well as simulation results based on the exact solution of the complex-valued viscoelastic guided wave problem. Two material models are discussed, namely the fractional Zener model and the anti-Zener model; we re-interpret the latter in terms of the Rayleigh damping model. Measurements are taken on a polypropylene sample and the proposed transient simulation model is used for inverse material characterization. The extracted material properties may then be used in computer-aided design of ultrasonic systems.
Keywords: viscoelasticity; ultrasonics; guided waves; inverse problem; scaled boundary finite element method

Transient modeling of ultrasonic guided waves in circular viscoelastic waveguides for inverse material characterization - Bause, Fabian; Gravenkamp, Hauke; Rautenberg, Jens; Henning, Bernd (Measurement Science and Technology)

Increasing the sensitivity of electrical impedance to piezoelectric material parameters with non-uniform electrical excitation. - Kulshreshtha, Kshitij; Jurgelucks, Benjamin; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten (Journal of Sensors and Sensor Systems)

Utilizing guided acoustic waves to measure dispersive material properties of polymers - Rautenberg, Jens; Bause, Fabian; Henning, Bernd (AMA~Conferences 2015)
This contribution will give a short introduction to the most important mechanic and acoustic parameters that are necessary to model and simulate frequency dependent sound propagation (dispersion) in isotropic but linear viscoelastic materials. Furthermore, several experimental techniques to measure these parameters will be discussed, like the dynamic-mechanical analysis and transient ultrasonic techniques. Finally it will be shown how to use the determined material parameters for the simulation of transient signals in a highly attenuative acoustic waveguide.

A High Performance SEU Tolerant Latch - Huang, Zhengfeng; Liang, Huaguo; Hellebrand, Sybille (Journal of Electronic Testing - Theory and Applications (JETTA))

Effiziente Auswahl von Testfrequenzen für den Test kleiner Verzögerungsfehler - Hellebrand, Sybille; Indlekofer, Thomas; Kampmann, Matthias; Kochte, Michael; Liu, Chang; Wunderlich, Hans-Joachim
Keywords: Workshop

Adaptive Playouts in Monte-Carlo Tree Search with Policy-Gradient Reinforcement Learning - Graf, Tobias; Platzner, Marco (Advances in Computer Games: 14th International Conference, ACG 2015, Leiden, The Netherlands, July 1-3, 2015, Revised Selected Papers)

Application of Automatic Differentiation for the inverse parameter identification of complex-valued forward models - Webersen, Manuel; Bause, Fabian; Henning, Bernd

Identification of temperature-dependent model parameters of ultrasonic piezo-composite transducers - Webersen, Manuel; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (AMA Conferences 2015)
When performing measurements, the effects of the measurement system itself on the measured data generally must be eliminated. Consequently, those effects, i.e. the system’s dynamic behavior, need to be known. For the piezo-composite transducers in an ultrasonic transmission line, a model based approach is used to describe their dynamic behavior and take into account its dependence on the environment temperature and the acoustic impedance of the target medium. Temperature-dependent model parameters are presented, which are obtained by performing a multiplepart identification process on the transducer model, based on electrical impedance measurements [1]. The identification process uses an inverse approach for optimizing a subset of the model parameters. Additionally, algorithmic differentiation methods are used to determine accurate derivatives. In a final optimization step, impedance measurements taken at different temperatures are used to determine the temperature dependencies of the model parameters. These can then be used to assess the plausibility of the identification results. Additionally, the parameters can be expressed as polynomials in the temperature to take different operating conditions into account.
Keywords: piezo-composite; transducer; temperature dependency; identification; plausibility

Implementation and uncertainty analysis of a test device for electrical impedance measurements using vector network analyzers - Webersen, Manuel; Karzellek, Michael; Bause, Fabian; Henning, Bernd

Case-Based Reasoning Research and Development - Hüllermeier, Eyke; Minor, M. (in Proceedings 23rd International Conference on Case-Based Reasoning (ICCBR 2015) LNAI 9343)

Proceedings 25. Workshop Computational Intelligence KIT Scientific Publishing - Hoffmann, F.; Hüllermeier, Eyke

Case Base Maintenance in Preference-Based CBR - Abdel-Aziz, A.; Hüllermeier, Eyke (In Proceedings 23rd International Conference on Case-Based Reasoning (ICCBR 2015))

Qualitative Multi-Armed Bandits: A Quantile-Based Approach - Szörényi, B.; Busa-Fekete, Robert; Weng, P.; Hüllermeier, Eyke (In Proceedings International Conference on Machine Learning (ICML 2015))

Dyad Ranking Using A Bilinear Plackett-Luce Model - Schäfer, Dirk; Hüllermeier, Eyke (in Proceedings European Conference on Machine Learning and Knowledge Discovery in Databases (ECML/PKDD))

Superset Learning Based on Generalized Loss Minimization - Hüllermeier, Eyke; Cheng, W. (in Proceedings European Conference on Machine Learning and Knowledge Discovery in Databases (ECML/PKDD))

Weighted Rank Correlation : A Flexible Approach Based on Fuzzy Order Relations - Henzgen, Sascha; Hüllermeier, Eyke (in Proceedings European Conference on Machine Learning and Knowledge Discovery in Databases (ECML/PKDD))

Online Rank Elicitation for Plackett-Luce: A Dueling Bandits Approach - Szörényi, B.; Busa-Fekete, Robert; Paul, Adil; Hüllermeier, Eyke (in Advances in Neural Information Processing Systems 28 (NIPS 2015))

Online F-Measure Optimization - Szörényi, B.; Busa-Fekete, Robert; Dembczynski, K.; Hüllermeier, Eyke (in Advances in Neural Information Processing Systems 28 (NIPS 2015))